Analysis and Exploration of the Industrial Development and Transformation Process of Historical Villages ——Taking Cuiwei Village as an Example - Junzhang Chen; Yile Chen; Liang Zheng (PT FORMOSA CENDEKIA GLOBAL, 2022)
Urban village is an important carrier of cultural heritage and a settlement space with regional characteristics. It can organically integrate and fully express the production and life and cultural customs of local residents. Taking Cuiwei historical village as an example, this study reasonably analyzes the problems encountered in the process of industrial development and transformation of historical villages, and provides reference for relevant departments.